The crayons trick or treat - Daywalt, Drew; Jeffers, Oliver (New York : Philomel Books, an imprint of Penguin Random House, 2022)
The crayons are ready to celebrate Halloween, but the don't know what to say when they knock on the door!
AD290L
Decoding demand: 67 (high) Semantic demand: 59 (medium) Syntactic demand: 29 (low) Structure demand: 79 (high)
Keywords: Crayons -- Juvenile fiction; Halloween -- Juvenile fiction; Crayons -- Fiction; Halloween -- Fiction; Picture books